Purification and characterization of TbHsp70.c, a novel Hsp70 from Trypanosoma brucei - Burger, Adélle (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
One of Africa's neglected tropical diseases, African Trypanosomiasis, is not only fatal but also has a crippling impact on economic development. Heat shock proteins play a wide range of roles in the cell and they are required to assist the parasite as it moves from a cold blooded insect vector to a warm blooded mammalian host. The expression of heat shock proteins increases during these heat shock conditions, and this is considered to play a role in differentiation of these vector-borne parasites. Heat shock protein 70 (Hsp70) is an important molecular chaperone that is involved in protein homeostasis, Hsp40 acts as a co-chaperone and stimulates its intrinsically weak ATPase activity. In silico analysis of the T. brucei genome has revealed the existence of 12 Hsp70 proteins and 65 Hsp40 proteins to date. A novel Hsp70, TbHsp70.c, was recently identified in T. brucei. Different from the prototypical Hsp70, TbHsp70.c contains an acidic substrate binding domain and lacks the C-terminal EEVD motif. By implication the substrate range and mechanism by which the substrates are recognized may be novel. The ability of a Type I Hsp40, Tbj2, to function as a co-chaperone of TbHsp70.c was investigated. The main objective of this study was to biochemically characterize TbHsp70.c and its partnership with Tbj2 to further enhance our knowledge of parasite biology. TbHsp70.c and Tbj2 were heterologously expressed and purified and both proteins displayed chaperone activities in their ability to suppress aggregation of thermolabile MDH. TbHsp70.c also suppressed aggregation of rhodanese. ATPase assays revealed that the ATPase activity of TbHsp70.c was stimulated by Tbj2. The targeted inhibition of the function of heat shock proteins is emerging as a tool to combat disease. The small molecule modulators quercetin and methylene blue are known to inhibit the ATPase activity of Hsp70. However, methylene blue did not significantly inhibit the ATPase activity of TbHsp70.c; while quercetin, did inhibit the ATPase activity. In vivo heat stress experiments indicated an up-regulation of the expression levels of TbHsp70.c. RNA interference studies showed partial knockdown of TbHsp70.c with no detrimental effect on the parasite. Fluorescence microscopy studies of TbHsp70.c showed a probable cytoplasmic subcellular localization. In this study both TbHsp70.c and Tbj2 demonstrated chaperone activity and Tbj2 possibly functions as a co-chaperone of TbHsp70.c.
Keywords: African trypanosomiasis -- Research; Heat shock proteins -- Research; Trypanosoma brucei -- Research; Mycobacterial diseases -- Research -- Africa; Parasitic diseases -- Africa -- Prevention; Parasites -- Physiology; Developing countries -- Economic conditions